Minimally invasive prosthetic restoration of posterior tooth loss with resin-bonded, wing-retained, and inlay-retained fixed dental prostheses fabricated from monolithic zirconia: a clinical report of two patients - Bömicke, Wolfgang; Karl, Jochen; Rammelsberg, Peter (The journal of prosthetic dentistry, 2017)
The esthetics and biocompatibility of ceramic resin-bonded fixed dental prostheses (RBFDPs) are regarded as better than those of their metal ceramic counterparts. However, a high incidence of complications in the posterior arches of ceramic RBFDPs initiated a process of continuous and evolving design development. This clinical report describes 2 successful restorations of a missing posterior tooth with monolithic zirconia RBFDPs with 2 different retainer designs: retentively prepared adhesive wings and inlays.